Ritual Pengikut Tarekat ShÃ¢dhilÃ®yah di Tambak Beras, Jombang-Jawa Timur - Safik, Abdullah (Program Studi Filsafat Agama Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2011)
This article tries to phenomenologically examines the existence of the Shâdhilîyah tarekat supervised by KH. Djamaluddin in Tambak Beras, Jombang. The Shâdhîlîyah tarekat, that had been initiated by Abû Hasan al-Shâdhilî, is an exceptional and consistent in holding and practicing its tawhid principle as well as dhikr rituals. In Indonesia, this tarekat has rapidly evolved. One of its murshid is KH. Abdul Jalil Mustaqim in Tulungagung, the murshid to KH. Djamaluddin. The tarekat has two main doctrines, are: firstly, ?ubûdîyah realm where its followers are obliged to phisically and mentally obey Allah swt and His messenger, i.e. the prophet Muhammad, in all their sayings and deeds. Secondly, mu?âmalah aspect where each follower is taught to interact with other people and creatures only for the sake of Allah. It means that the tarekat is a medium of self approaching to Allah. One of special rites (khusûsîyah) conducted by this tarekat is an every-Tuesday agenda where dhikr, tawassul, tahlîl, and tahmîd activities are held. Technically, a sâlik when s/he recites dhikr should be followed by breathing in which is concentrated in the navel and going on top through thoracic cavity and coming out through the mouth then retracting it back to tongue.